Creep Behavior of Fiber Reinforced Mortars and Its Effect to Reduce the Differential Shrinkage Stress - Senot Sangadji; Endah Safitri; Muhammad Z. Arifin; Stefanus A. Kristiawan (Civil Engineering Journal, 2023)
This research aims to develop durable repair materials that can resist shrinkage cracking by exploring the role of creep in reducing shrinkage stress. In this regard, the creep effect can only be quantified if an accurate creep prediction model and theoretical analysis of the shrinkage stress in the patch repair system exist. For this purpose, the research was carried out in the following sequences: first, the research investigated the short-term creep of the patch repair materials containing accelerator and micro-synthetic fibers in the 0.00â€“0.12% volume fraction range. This short-term creep was measured on five-cylinder specimens (having a diameter of 75 mm and a height of 275 mm). Three specimens were used to determine the deformation of the repair material under unloading conditions, while those remaining were used to determine the total deformation under loading conditions. The amount of creep deformation was determined by taking away the unloaded (shrinkage) and instantaneous (elastic) deformations from the total deformation of the loaded specimens. Secondly, a modified prediction model of ACI 209R-08 is introduced to accurately capture the rate and magnitude of the observed creep of the repair materials. Finally, a formulated theoretical analysis of shrinkage stress in the patch repair system was proposed to examine how creep potentially reduces the repair material's cracking tendency. The results show that the asymptotic value of the creep curve is attained at an earlier age and that its magnitude is greater than that of most concrete. The modified ACI 209R-08 prediction model can closely estimate the repair materials' creep behavior. The best-fit line, residual values, and coefficient of error analyses confirm the modified model's prediction accuracy. The analysis of tensile stress development in the repair layer suggests that creep can reduce stress by up to 50%. With such a reduction, the repair material is expected to be durable in resisting shrinkage and cracking tendency.Â Doi: 10.28991/CEJ-2023-09-08-014 Full Text: PDF